2018
DOI: 10.1007/s00270-018-2118-6
|View full text |Cite|
|
Sign up to set email alerts
|

Reason of Discontinuation After Transarterial Chemoembolization Influences Survival in Patients with Hepatocellular Carcinoma

Abstract: BackgroundTransarterial chemoembolization (TACE) for intermediate-stage hepatocellular carcinoma (HCC) is often repeated until unTACEable progression (UTP) occurs. There is little data on the various reasons for stopping TACE and its consequences for subsequent treatment and survival.AimTo assess the impact of the various reasons of UTP on survival and consequences for subsequent treatments.MethodsConsecutive HCC patients who underwent TACE between 2003 and 2016 were analyzed retrospectively for the reason of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The importance of retreatment is highlighted in current guidelines and as long as no significant reduction in performance score or liver function occurs it is recommended to perform at least two TACE procedures before evaluating a patient as a "non-responder" (141,223). Further, untreatable progression post TACE (so-called "unTACEable" progression) is related to radiological tumor progression, deterioration of liver function or performance status (41), where in a recent study intrahepatic tumor progression was the most common reason while the liver function and performance status more often were preserved (224). This is important as most of these patients can be considered for alternative treatments, and it is essential to consider the liver function when evaluating a patient for TACE retreatment.…”
Section: Study 3 -Dee-tace In Hepatocellular Carcinoma and Treatment mentioning
confidence: 99%
“…The importance of retreatment is highlighted in current guidelines and as long as no significant reduction in performance score or liver function occurs it is recommended to perform at least two TACE procedures before evaluating a patient as a "non-responder" (141,223). Further, untreatable progression post TACE (so-called "unTACEable" progression) is related to radiological tumor progression, deterioration of liver function or performance status (41), where in a recent study intrahepatic tumor progression was the most common reason while the liver function and performance status more often were preserved (224). This is important as most of these patients can be considered for alternative treatments, and it is essential to consider the liver function when evaluating a patient for TACE retreatment.…”
Section: Study 3 -Dee-tace In Hepatocellular Carcinoma and Treatment mentioning
confidence: 99%
“…This leads us to the hypothesis that, during the course of disease, especially the liver function becomes more important as a treatment-limiting factor. Several studies have previously shown that a worsening of Child-Pugh score and ALBI score after the initial TACE is correlated with an impaired median OS and progression-free survival [ 31 36 ]. Furthermore, previous results by Labeur et al indicate that patients with intrahepatic tumor progression but preserved liver function are more often able to receive further locoregional or systemic treatment beyond TACE, while patients with a worsening of the liver function are “unlikely to benefit from the currently available subsequent treatments” [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, these different models identified a first group of patients accounting for around 50% of our population who benefit sustainably from TACE, as this treatment may sometimes lead to complete tumor necrosis[ 22 ]. However, local and/or distant intrahepatic recurrences are commonly observed including in patients who achieved complete response following TACE[ 5 ]. These recurrences sometimes have a more invasive pattern[ 23 ], and became TACE resistant.…”
Section: Discussionmentioning
confidence: 99%
“…However limitations in its ability both to guide this procedure and more generally to manage intermediate-stage HCCs are recognized[ 3 ]. Despite serious improvements in patient selection, TACE modalities, efficacy [using modified response evaluation criteria in solid tumors (mRECIST)][ 4 ] and discontinuation criteria[ 5 ], this treatment usually fails to achieve sustained control of the disease, despite an objective response in about 50% of patients[ 6 ]. Despite subclassification propositions for intermediate stages[ 7 , 8 ] using up-to-seven criteria arbitrarily, clinicians have also continued to promote scores both to refine individual prognosis and guide therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%